The dark side of leadership: How ineffective training and poor ethics education trigger unethical behavior? - Benlahcene, Abderrahmane; Saoula, Oussama; Jaganathan, Mathivannan; Ramdani, Abbas; AlQershi, Nagwan Abdulwahab (Frontiers in Psychology, 2022)
The challenge of restricting unethical behaviour requires public companies to reinforce ethical practices among leaders through various instruments. Previous research suggests that the (un)ethical behaviour of leaders can be influenced by many situational factors. This study aimed to investigate the influence of ethics training and education on unethical leadership behaviour. Data were collected through semi-structured interviews with 15 leaders from public companies in Algeria. Data analysis was facilitated using ATLAS. ti 8 qualitative analysis software. The findings show that public companies in Algeria suffer from several issues related to leaders’ ethics training and education. The findings also indicate that some of these unethical leadership behaviours are the result of ineffective training programs and poor ethics education within public companies. The absence or ineffectiveness of ethics training and education within and outside organizational settings has a detrimental impact on leaders’ ethical character. This study is the first to explore how public companies in Algeria engage in ethical training and leadership education. The different sectors of the Algerian business can use the findings as a point of reference to embed the appropriate ethical climate in their respective organizations.